2009
DOI: 10.1097/chi.0b013e31819b3848
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Identification Among Children With an Autism Spectrum Disorder: Findings From a Population-Based Surveillance Study

Abstract: Objective At what age are children with an autism spectrum disorder (ASD) identified by community providers? What factors influence the timing of when children are identified with ASDs? This study examined the timing of when children with ASDs are identified. Method Data came from 13 sites participating in the Centers for Disease Control and Prevention’s 2002 multisite, ongoing autism surveillance program, the Autism and Developmental Disabilities Monitoring Network. Survival analysis was used to examine fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

46
370
4
16

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 511 publications
(452 citation statements)
references
References 13 publications
46
370
4
16
Order By: Relevance
“…7 However, late identification of ASD is a wellknown problem, even in developed countries. 8 A recent review article including data from 42 studies (from 1990 to 2012) showed that the mean age of ASD diagnosis ranged from 38 to 120 months. 9 In Brazil, data on the age at ASD diagnosis and on the ability of primary care providers to detect ASD are practically nonexistent.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, late identification of ASD is a wellknown problem, even in developed countries. 8 A recent review article including data from 42 studies (from 1990 to 2012) showed that the mean age of ASD diagnosis ranged from 38 to 120 months. 9 In Brazil, data on the age at ASD diagnosis and on the ability of primary care providers to detect ASD are practically nonexistent.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that diagnosis of autism by age 3, and even by age 2, is stable over time (Chawarska et al 2007;Kleinman et al 2008). However, the median age of identification is 5.7 years (Shattuck et al 2009). In a cohort of children younger than 12 years of age in Flanders, the Dutch-speaking region of Belgium, the average age of autism diagnosis was 5.9 years (Roeyers 2008).…”
mentioning
confidence: 99%
“…This has also been noted in other studies (14,17), and it may be due to the fact that young children with delayed developmental milestones are more likely to be referred to specialist pediatric services with greater expertise in recognizing and diagnosing AD at an earlier age.…”
Section: Discussionmentioning
confidence: 78%
“…AD can reliably be diagnosed by experienced clinicians in children 3 years old or younger (14). However, the average age at AD diagnosis varies across studies from 3.1 years (15) to 4.8 years (16) to 5.2 years (17) in accordance with sample characteristics and ascertainment methods (18,19).…”
Section: Introductionmentioning
confidence: 99%